Exercise addiction and self-esteem in individuals exercising - Katra, Haşim (Journal of Dependence, 2021)
Objective: The aim of this study was to determine the exercise addiction level and self-esteem of individuals who exercise, and to examine correlations and differences with different variables.Method: A total of 202 people exercising in sports centers located in Çanakkale provincial center participated in the research. Data collection tools used in the research included the Exercise Addiction Scale and Rosenberg SelfEsteem Scale.Results: Gender variable was determined to have no effect on exercise addiction and self-esteem. According to the marital status variable, participants were determined to have significant differences in postponement of individualsocial needs and conflict points. There was a significant correlation identified between the age variable and selfesteem points. Individuals participating in exercise were determined to have a positive significant correlation between frequency of exercise and exercise age with exercise addiction.Conclusion: Individuals who exercise were a dependent group in terms of exercise addiction and had high selfesteem points, while exercise addiction levels increased with the increase in weekly exercise duration and months of participation in exercise. Additionally, among individuals who exercise, single individuals were concluded to postpone individual and social needs for participation in exercise.
Keywords: Exercise; exercise addiction; self-esteem